Faktor yang mempengaruhi tingginya prevalensi penggunaan metode kontrasepsi suntik di Indonesia (analisis data PMA 2020) - Harahap, Yanna Wari; Harahap, Olivia Feby Mon (Universitas Aufa Royhan, 2018)
The injectable contraceptive method is the most widely used, followed by pills from 1991 until now. The prevalence of injection contraceptive use in 2015 and 2016 increased from 52.6% to 53.6%. While the percentage of long-term contraceptive use (IUD, implant, and MOW) is below 10%. Factors that influence contraceptive use are age, education, knowledge, number of living children, availability of contraception, support from health workers, husband and wife agreement and side effects. Health worker support can be applied by providing information about family planning. This study analyzes the relationship of providing information with injectable contraceptive use in Indonesia. The cross-sectional study used PMA2020 survey data conducted in May-October 2015. The sample of the study was WUS which was selected by a two-stage randomized method, according to the inclusion and exclusion criteria of 3,621 respondents. Multivariate analysis was used namely logistic regression by considering variables of age, parity, and education. The use of WUS counterparts is high on injections. Providing information to WUS about contraception more than 60% gets bad information. Proper information on WUS has a chance of 1.15 times greater use of injectable contraception than WUS with poor information, with a p-value of 0.046. The effect of giving information with the good category is 1.28 times more likely to use injection contraception than WUS by giving bad information after considering other variables (age, parity, and education). The provision of information on WUS needs to be increased by health workers/family planning officers because providing complete information to prospective users can help clients choose contraceptive methods that are appropriate to their conditions.